The Characteristics of Material DSSC (Dye-Sensitized Solar Cell) Solar Cell from Extraction of Teak Leaves - Kusuma, Hamdan Hadi (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2016)
The research of solar cell with using dye from natural materials as a sensitizer in a dye-sensitized solar cell (DSSC) continues to grow. One advantage of the DSSC is does not require a material with high purity so that the production cost is relatively low. This research aims to analyze the characteristics of the absorption band of teak leaf extract. Extraction of teak leaves dissolved in a mixture of ethanol and acetic acid with a variation ratio of 1: 0, 1: 1 and 5.66: 1, resulting in a solution of each color reddish yellow, reddish brown and dark red. Absropsi test results with UV-Vis spectrometer showed that there are peaks in the absorbance in the visible region, ie at wavelengths between 500 nm to 560 nm. This shows that the dye material of teak leaf extract may work or absorb the green color. While absobption other peaks are also found in pektrum wavelength of 580 nm, 600 nm and 660 nm, each of which can absorb the green color yellow, orange and red. Â©2016 JNSMR UIN Walisongo. All rights reserved.